Excitatory-Inhibitory Homeostasis and Diaschisis: Tying the Local and Global Scales in the Post-stroke Cortex - Páscoa dos Santos, Francisco; Verschure, Paul F. M. J. (Frontiers in Systems Neuroscience, 2022)
Maintaining a balance between excitatory and inhibitory activity is an essential feature of neural networks in the human cortex. In the face of perturbations in the levels of excitation to cortical neurons, synapses are adjusted to maintain excitatory-inhibitory (EI) balance. In this review, we summarize research on this EI homeostasis in the human cortex, using stroke as our case study, because of the loss of excitation to distant cortical regions after focal lesions. Widespread changes following a localized lesion, a phenomenon known as diaschisis, are not only related to excitability, but also observed with respect to functional networks. Here, we highlight the main findings regarding the evolution of excitability and functional networks during the process of post-stroke recovery, and how both are related to functional recovery. We show that cortical reorganization at a global scale can be explained from the perspective of EI homeostasis. Indeed, recovery of functional networks is paralleled by increases in excitability across the cortex. These adaptive changes result from plasticity mechanisms such as synaptic scaling and are linked to EI homeostasis, providing a possible target for future therapeutic strategies in the process of rehabilitation. In addition, we address the difficulty of simultaneously studying these multiscale processes by presenting recent advances in large-scale modeling of the human cortex in the contexts of stroke and EI homeostasis, suggesting computational modeling as a powerful tool to tie the meso- and macro-scale processes of recovery in stroke patients.